Evidence for the alloimmune basis and prognostic significance of Borderline T cell–mediated rejection. Issue 9 (9th April 2020) - Wiebe, Chris; Rush, David N.; Gibson, Ian W.; Pochinco, Denise; Birk, Patricia E.; Goldberg, Aviva; Blydt‐Hansen, Tom; Karpinski, Martin; Shaw, Jamie; Ho, Julie; Nickerson, Peter W.
Abstract : Prognostic biomarkers of T cell–mediated rejection (TCMR) have not been adequately studied in the modern era. We evaluated 803 renal transplant recipients and correlated HLA‐DR/DQ molecular mismatch alloimmune risk categories (low, intermediate, high) with the severity, frequency, and persistence of TCMR. Allograft survival was reduced in recipients with Banff Borderline (hazard ratio [HR] 2.4, P = .003) and Banff ≥ IA TCMR (HR 4.3, P < .0001) including a subset who never developed de novo donor‐specific antibodies ( P = .002). HLA‐DR/DQ molecular mismatch alloimmune risk categories were multivariate correlates of Banff Borderline and Banff ≥ IA TCMR and correlated with the severity and frequency of rejection episodes. Recipient age, HLA‐DR/DQ molecular mismatch category, and cyclosporin vs tacrolimus immunosuppression were independent correlates of Banff Borderline and Banff ≥ IA TCMR. In the subset treated with tacrolimus (720/803) recipient age, HLA‐DR/DQ molecular mismatch category, and tacrolimus coefficient of variation were independent correlates of TCMR. The correlation of HLA‐DR/DQ molecular mismatch category with TCMR, including Borderline, provides evidence for their alloimmune basis. HLA‐DR/DQ molecular mismatch may represent a precise prognostic biomarker that can be applied to tailor immunosuppression or design clinical trials based on individual patient risk. Abstract : Alloimmune risk categorization using HLA‐DR/DQ molecular mismatch risk correlates with the severity, frequency, and persistence of T cell–mediated rejection and with graft survival, independent of de novo DSA.